Comparative mechanical behavior of human ankle ligaments - (:unkn) unknown (Springer Verlag, 2007)
Four different ankle ligaments obtained from human cadavers were kept in a physiological solution until mechanical tests were run by using Instron Universal Testing Machine. Addition to conventional tensile tests, cyclic loadings under load control were applied. Prior all the tests run, on each ligament a matrix type of markings were created, so that, not only bulk mechanical properties, properties of individual different parts of ligaments have been obtained as function of stress, strain and time. Results obtained from matrix mentioned are directly related with the anisotropic properties of ligaments. A computer program was prepared to analyze the displacements. During experiments a video camera connected to the computer was used to record the data analyzed after experiments run. All the ligaments behaved differently. Each one also showed highly anisotropic behavior. It is also observed that sudden strain rate changes caused changes in stiffness. © International Federation for Medical and Biological Engineering 2007.
Keywords: Ankle; Ligament; Mechanical behavior